2016
DOI: 10.1097/jcp.0000000000000492
|View full text |Cite
|
Sign up to set email alerts
|

Tamoxifen

Abstract: Tamoxifen can be considered an effective treatment for manic bipolar patients. Making a conclusion regarding the efficacy and safety for longer periods warrants further studies with a larger sample size and longer follow-up duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Furthermore, TMX has also been reported to be an effective antimanic treatment in pediatric population [80]. In a recent meta-analysis, TMX was found to be effective as monotherapy and as an adjunctive treatment for manic symptoms [13]. Recently, monotherapy with endoxifen, a metabolite of TMX and a potent PKC inhibitor [81], was found to be as effective as with valproic acid (extended release 1,000 mg/day) in mitigation of manic symptoms [82].…”
Section: Pkc Translocation and Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, TMX has also been reported to be an effective antimanic treatment in pediatric population [80]. In a recent meta-analysis, TMX was found to be effective as monotherapy and as an adjunctive treatment for manic symptoms [13]. Recently, monotherapy with endoxifen, a metabolite of TMX and a potent PKC inhibitor [81], was found to be as effective as with valproic acid (extended release 1,000 mg/day) in mitigation of manic symptoms [82].…”
Section: Pkc Translocation and Activitymentioning
confidence: 99%
“…Our advances in neuroimaging techniques, such as in vivo magnetic resonance imaging, and novel genetic approach, such as convergent functional genomics, are providing us endophenotypic characteristics of BD [11]. After 3 decades of intensive preclinical and translational research, protein kinase C (PKC) has come to be recognized to play a central role in the pathophysiology of BD [12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Tamoxifen is downgraded because of the risk of uterine cancer and the lack of clinical experience despite evidence for efficacy. Combination treatments with carbamazepine or oxcarbazepine (level 3),163 haloperidol (level 2),144, 164 or tamoxifen (level 2)165 plus lithium or divalproex are also included as third‐line. Repetitive transcranial magnetic stimulation (rTMS) in the right prefrontal cortex at 110% motor threshold (level 3)166 can also be considered in combination with pharmacotherapy.…”
Section: Acute Management Of Bipolar Maniamentioning
confidence: 99%
“…Three additional trials have been carried out to test the effectiveness of tamoxifen either as an adjunct- or mono- therapy. A meta-analysis of these three trials as well as the two described above observed that tamoxifen is an effective treatment for bipolar mania in both males and females, but that further studies utilizing a larger sample size and a longer follow up duration will be necessary to make any conclusions as to its safety and efficacy (Talaei et al, 2016). It is also worth noting that in one trial, the efficacy of tamoxifen in treating bipolar mania was specific and not mimicked by the antiestrogen medroxyprogesterone which does not inhibit PKC (Kulkarni et al, 2006).…”
Section: Therapeutic Utility Of Tamoxifen In Inhibiting Maniamentioning
confidence: 99%